Photo-chemical transport modelling of tropospheric ozone: A review - Sharma, Sumit; Sharma, Prateek; Khare, Mukesh (Atmospheric environment (1994), 2017)
Ground level ozone (GLO), a secondary pollutant having adverse impact on human health, ecology, and agricultural productivity, apart from being a major contributor to global warming, has been a subject matter of several studies. In order to identify appropriate strategies to control GLO levels, accurate assessment and prediction is essential, for which elaborate simulation and modelling is required. Several studies have been undertaken in the past to simulate GLO levels at different scales and for various applications. It is important to evaluate these studies, widely spread over in literature. This paper aims to critically review various studies that have been undertaken, especially in the past 15 years (2000–15) to model GLO. The review has been done of the studies that range over different spatial scales – urban to regional and continental to global. It also includes a review of performance evaluation and sensitivity analysis of photo-chemical transport models in order to assess the extent of application of these models and their predictive capability. The review indicates following major findings: (a) models tend to over-estimate the night-time GLO concentrations due to limited titration of GLO with NO within the model; (b) dominance of contribution from far-off regional sources to average ozone concentration in the urban region and higher contribution of local sources during days of high ozone episodes; requiring strategies for controlling precursor emissions at both regional and local scales; (c) greater influence of NOx over VOC in export of ozone from urban regions due to shifting of urban plumes from VOC-sensitive regime to NOx-sensitive as they move out from city centres to neighbouring rural regions; (d) models with finer resolution inputs perform better to a certain extent, however, further improvement in resolutions (beyond 10 km) did not show improvement always; (e) future projections show an increase in GLO concentrations mainly due to rise in temperatures and biogenic VOC emissions. •Review of studies using photo-chemical models at urban, regional and global scales.•Review of performance and sensitivities of the photo-chemical models.•Seasonal, diurnal, and spatial analysis of model predictions.•Future projections of ozone due to temperatures and biogenic emissions.